A New Paradigm for Economic Sustainability in Riau: Productive Zakat as a Mechanism for Social Development - Dewi Puspa Suri; Kamaliah Kamaliah; Edyanus Herman Halim (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2024)
This study aims to analyze the impact of mustahiq independence, assess the effects of economic sustainability, and evaluate the synergy of the pentahelix model on the acceptance and utilization of productive zakat funds to enhance long-term effectiveness, efficiency, and welfare. The population consists of 28,087 recipients of BAZNAS productive zakat programs in Riau Province, employing Quota Sampling to ensure group representation. Data analysis is conducted using PLS-SEM (Partial Least Squares - Structural Equation Modeling) to assess the program's effects on economic independence and sustainability. The findings indicate that mustahiq independence, sustainability, and pentahelix synergy significantly influence productive zakat programs. However, only pentahelix synergy demonstrates a positive impact, while independence and sustainability have negative influences. This study’s novelty lies in its quantitative, holistic approach to measuring independence, sustainability, and pentahelix synergy. Additionally, the development of specific indicators for these variables is a new contribution, providing a foundation for future research employing robust statistical methods to enhance accuracy and relevance in diverse contexts.